SPOROTRIKOSIS LIMFOKUTAN DIAGNOSIS HISTOPATOLOGI DAN SITOLOGI - Lintong, Poppy M.; Sumolang, Inneke V. (UNIVERSITAS SAM RATULANGI, 2010)
Abstract: Diagnosis of sporotrichosis associated with lymphocutaneous nodules was made based on the histopathological examination of skin lesions and the cytology of fine needle aspiration biopsy (FNAB). A case of sporotrichosis in a 63-year-old man was reported with papules and nodules spread along the back of the left hand, forearm, and arm. The histopatho-logical examination showed infiltration of PMNs, granulomas, and giant cells in the dermis and epidermis, along with hyperplasia and microabscesses. Sporothrix schenckii was not found in the skin lesion tissues. However, in the FNAB cytology examination of lymphocutaneus nodules we found spores of Sporothrix schenckii in the cytoplasma of histiocytes besides granuloma and infiltration of PMNs. Key words: sporothrix schenckii, histopathology, FNAB cytology.Â Abstrak: Diagnosis sporotrikosis kulit dengan nodul limfokutan ditegakkan melalui pemerik-saan histopatologi pada lesi kulit dan sitologi biopsi aspirasi jarum halus pada nodul limfo-kutan. Kami melaporkan kasus sporotrikosis pada laki-laki berusia 63 tahun dengan papul-papul dan nodul-nodul eritematosa pada dorsum manus, antebrakium, dan brakium sinistra. Pemeriksaan histopatologi jaringan biopsi dari lesi kulit menunjukkan reaksi radang, gambaran granuloma, dan sel datia dalam dermis dan epidermis, dengan mikroabses disertai hiperplasia. Tidak ditemukan jamur Sporothrix schenckii dalam potongan jaringan histopatologi. Hasil pemeriksaan sitologi biopsi aspirasi jarum halus pada nodul limfokutan memperlihatkan adanya spora-spora jamur Sporothrix schenckii dalam sitoplasma sel-sel histiosit disampingÂ terdapatnya bentuk granuloma dalam infiltrat radang. Kata kunci: sporothrix schenckii, histopatologi, sitologi biopsi aspirasi jarum halus.